2015
DOI: 10.1051/swsc/2015027
|View full text |Cite
|
Sign up to set email alerts
|

The auroral red line polarisation: modelling and measurements

Abstract: In this work, we model the polarisation of the auroral red line using the electron impact theory developed by Bommier et al. (2011). This theory enables the computation of the distribution of the Degree of Linear Polarisation (DoLP) as a function of height if the flux of precipitated electrons is provided as input. An electron transport code is used to infer the stationary electron flux at each altitude in the ionosphere as a function of energy and pitch angle. Using adequate cross-sections, the integral of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…This have been performed for the night of March 2nd. The DoLP in this case is 4.6% ± 0.9% with the ratio method which is in the same order of magnitude compared to previous measurements of the red line DoLP (Lilensten et al, 2008(Lilensten et al, , 2015.…”
Section: Additional Checkssupporting
confidence: 83%
See 1 more Smart Citation
“…This have been performed for the night of March 2nd. The DoLP in this case is 4.6% ± 0.9% with the ratio method which is in the same order of magnitude compared to previous measurements of the red line DoLP (Lilensten et al, 2008(Lilensten et al, , 2015.…”
Section: Additional Checkssupporting
confidence: 83%
“…Subsequent observations (e.g., Barthelemy et al, 2011) confirmed that the red line is polarized at a level of 2-3% with significant variations on short time scales. This new observable could be useful either to monitor the response of the upper atmosphere to particle precipitations (Lilensten et al, 2015) or possibly to map the variations of the direction of the local magnetic field during geomagnetic activity (Lilensten et al, 2016). Polarization is always linked to some anisotropy, either in the emission process itself or along the line-of-sight.…”
Section: Introductionmentioning
confidence: 99%
“…The red line is the signal reconstructed from a cos2 fit on the filtered data as in Lilensten et al []. The black line is the signal reconstructed from the Stockes parameters deduced with a time‐dependent Mueller method as in Lilensten et al []. (top) The polarization lens orientation (with respect to the vertical axis) was 0°.…”
Section: The 2015 Ny‐ålesund Campaignmentioning
confidence: 99%
“…The process was later improved in Lilensten et al [2013] to take account of the instrumental polarization using the Mueller formalism [Goldstein, 2003;Stenflo, 1994;Martinez Herrero et al, 2009;Clarke, 2010]. Recently, this latter approach was again improved by taking into account the temporal variability of the polarization during the rotation of the polarizing lens [Lilensten et al, 2015]. All three data processing are still used and are compared in Figure 2 on a set of calibration tests where an additional polarization lens was placed in front of the polarized channel and oriented along different angles with respect to the vertical axis.…”
Section: Data Processing and Calibration Of Sppmentioning
confidence: 99%
See 1 more Smart Citation